CONCEPTS OF IMPROVING CURRENT PROTECTION OF POWER-GRID LINES - F. A. Romaniuk; M. A. Shevaldin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The  6–35  kV  power-grid  current  protection  serves  to  protect  the  transmission  lines against phase-to-phase short-circuits. The major disadvantage of it lies in the relatively large time delays of the last stages especially in the main sections of the grid owing to the stepped relay characteristics as well as a large number of the steps. A full-fledged protection of the 6–35 kV lines against inter-phase short circuits can be provided by the two-stage current protection: the first stage being the current cutoff without any time delay and the second stage – the maximum current protection where the time delay is linear contingent on the distance between the protection placement and the fault-point location. The article introduces the rating formulae for the time delays of the second-stage and their exemplary graphic presentation. The authors offer a variant for solving the problem with computation of the second-stage time delays in those instances where several feeders diverge from the bus bars of the substation located in the end of the protected line.Improving current protections for the 6–35 kV transmission lines with one-end power supply against interphase short-circuits can be based on the collective application of the following principles: accounting for the type and location of the short-circuit which provides for the high-performance cutoff zone instantaneous expansion and its independence on the mode of failure and the grid operation mode. It also allows increase of the last stage sensitiveness towards asymmetrical short-circuits; detection of the short-circuit location only on the results of fault currents measurement which simplifies the protection implementation; realization of the last (second) protection stage with linear-dependent time delay which ensures potentiality of its operation speed increase.